PERAN GOOD GOVERNMENT GOVERNANCE DALAM MEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA PEMERINTAH KOTA DENPASAR - Widiari, Putu Ayu; Badera, I Dewa Nyoman; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research analyzed the role of Good Government Governance (GGG) strengthening Budgeting Participation towards performance of Denpasar Municipality. Population of this research was all of local government working unit in Denpasar Municipality. Sample was 44 using total sampling technique. Data collection technique was survey method using questionnaires. Hypotheses were tested empirically using Moderated Regression Analysis (MRA). Result of research shows that budgeting participation significantly influenced towards performance of Denpasar Municipality. Good Government Governance significantly influence towards performance of Denpasar Municipality. The result also shows that Good Government Governance strengthening budgeting participation towards performance of Denpasar Municipality.
Keywords: Good Government Governance, Participation Budgeting, Government Performance